Tanishq : pricing, retail selling and inventory management of jewellery - Tiwari, Tara, (SAGE Business Cases., 2020)
The Indian jewellery market is highly fragmented and ruled over by local players. Many unethical practices exist in the jewellery market, like the undercaratage of gold, misrepresentation of quality, etc. Tanishq, part of the Tata Group, is known for maintaining high ethical standards and delivering value to its customers through fair and transparent practices. It has a 6% share in the Indian jewellery retail market.